2016
DOI: 10.1021/acs.langmuir.6b00373
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Core–Silica Shell Particles with Defined Nanoarchitectures as a Versatile Platform for Suspension Array Technology

Abstract: The need for rapid and high-throughput screening in analytical laboratories has led to significant growth in interest in suspension array technologies (SATs), especially with regard to cytometric assays targeting a low to medium number of analytes. Such SAT or bead-based assays rely on spherical objects that constitute the analytical platform. Usually, functionalized polymer or silica (SiO2) microbeads are used which each have distinct advantages and drawbacks. In this paper, we present a straightforward synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 60 publications
(123 reference statements)
3
54
0
Order By: Relevance
“…For example, layer-by-layer (LBL) assembly through sequential adsorption of polyelectrolytes (PELs) has been utilized to generate electrostatic attraction 31 33 . Surface modification based on the treatment of the amphiphilic coupling agent with preformed polymer particles are demonstrated to increase chemical affinity through van der Waals force, hydrogen bonding and dipole-dipole interaction 34 36 . Additionally, the synthetic procedures commonly require significant affinity between the inorganic silica particles and polymers to circumvent their inherent incompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…For example, layer-by-layer (LBL) assembly through sequential adsorption of polyelectrolytes (PELs) has been utilized to generate electrostatic attraction 31 33 . Surface modification based on the treatment of the amphiphilic coupling agent with preformed polymer particles are demonstrated to increase chemical affinity through van der Waals force, hydrogen bonding and dipole-dipole interaction 34 36 . Additionally, the synthetic procedures commonly require significant affinity between the inorganic silica particles and polymers to circumvent their inherent incompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction indicates that RB occupies the mesoporous channels of RB@MSNs, thus decreasing the total pore volume without complete clogging of the pores. The percentage of RB grafted to MSNs was estimated by thermogravimetric analysis (see Supporting Information, Figure S9b) after thorough washing sequences to remove any non‐grafted RB (Soxhlet). RB@MSNs samples were preheated at 350 °C, and the mass loss was measured between 400 °C and 800 °C.…”
Section: Resultsmentioning
confidence: 99%
“…MgSO 4 and KPS were used as received. Molar concentrations used for MgSO 4 and KPS (0.0051 M and 0.0005 M, respectively) were investigated prior to conducting mechanistic studies to achieve a desired particle size of 1 lm (results not reported here). The relative monomer composition and addition times in hours for each monomer are listed in Table 1.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…INTRODUCTION Polystyrene latex microspheres (PSLs) are used in applications ranging from high-performance chromatography column packing materials to seeding materials for airflow velocity measurements in wind tunnels, as well as in drug-delivery and for other biomedical purposes. [1][2][3][4][5][6] NASA has particular interest in these meso-scaled materials due to their ubiquitous use, low production cost and complexity, and the large number of nearly geometrically identical particles that can be produced. The broad range of applications of polymeric microspheres has led to an extensive investigation of their synthesis, characterization, and properties for diverse uses.…”
mentioning
confidence: 99%